Organic-inorganic hybrid perovskite glass for high-energy ray imaging and preparation method thereof

The preparation of organic-inorganic hybrid perovskite glass by diffusion method and low-temperature melting method solves the problem of preparing perovskite glass with high transparency and good scintillation performance in the prior art, and achieves efficient preparation without the protection of inert gas in the air, with excellent stability and low production costs.

CN119529822APending Publication Date: 2025-02-28WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714393.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to prepare perovskite glass for high-energy ray imaging with high transparency, good scintillation performance and large area coverage, and the production process is complex and the equipment requirements are high.

Method used

Organic-inorganic hybrid perovskite glass is synthesized by diffusion method, and transparent glass is prepared by low-temperature melting method. The chemical formula is AxByCz:Dm, where A is an organic group containing C, H, P, O, etc., B is a divalent metal ion Zn2+, C is a halogen element Cl- or Br-, and D is a doping element Mn2+, Sb3+ or Cu+, and it is protected without inert gas in the air.

Benefits of technology

The preparation of organic-inorganic hybrid perovskite glass with high transparency, good scintillation performance and large area coverage in the air is achieved, with a wide range of linear dose rate response, low detection limit and excellent stability, reducing production costs and simplifying equipment requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529822A_ABST
    Figure CN119529822A_ABST
Patent Text Reader

Abstract

The invention provides organic-inorganic hybrid perovskite (OIHP) glass for high-energy ray imaging and a preparation method of the organic-inorganic hybrid perovskite (OIHP) glass. A is an organic group containing C, H, P, O and the like, B is a divalent metal ion Zn < 2 + >, C is a halogen element Cl <-> or Br <->, D is a doping element Mn < 2 + >, Sb < 3 + > or Cu < + >, x is equal to 2, y is equal to 1, z is equal to 4-9, and m is equal to 0-1. The OIHP glass takes Sb < 3 + >, Mn < 2 + > or Cu < + > as active ions, and can be used for imaging of high-energy rays including X-rays. According to the OIHP glass and the preparation method thereof, the whole process is carried out in air, inert gas protection is not needed, the product is transparent under visible light, bright orange light, green light or yellow light can be emitted under an ultraviolet lamp, and the OIHP glass has wide-range linear dose rate response, low detection limit and excellent stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of organic-inorganic hybrid glass, in particular to an organic-inorganic hybrid perovskite glass for high-energy ray imaging and a preparation method thereof, which can be applied to high-energy ray imaging and multi-color lighting; and belongs to organic-inorganic hybrid perovskite solid materials. Background Art

[0002] In recent years, with the development of digital medicine and other industrial and scientific high-energy ray detection imaging scenarios, high-performance high-energy ray imagers have attracted great attention. High-energy rays are widely used in various fields due to their penetrating ability, such as medical radiation diagnosis, industrial detection, and security inspection. However, due to their invisibility, high-energy ray signals must be converted into electrical signals or visible light to obtain image information. Traditional scintillators, such as Bi4Ge3O 12 (BGO), CsI:Tl and Lu3Al5O 12 LuAG:Ce consists mainly of inorganic crystals. Despite offering high light yields and good stability, their production is hampered by harsh crystal growth conditions. As a result, there is an increasing demand for next-generation refrigerators that can overcome these limitations. In addition, the fabrication of large-area refrigerators remains challenging. For almost all media, high-energy rays have a refractive index close to 1, which means that it does not refract and is difficult to focus. This necessitates the use of large-area devices for imaging applications.

[0003] Generally speaking, high-energy ray scintillating screens made of perovskite crystals are produced by grinding perovskite crystals into powder and then pressing them into polycrystalline screens. Alternatively, some use organic polymers such as polystyrene, polyvinyl butyral, and poly(methyl methacrylate) as binders. However, the scintillating films prepared by these methods usually show low transparency, exhibit severe light scattering, and reduce imaging quality. Currently, most reported scintillating films based on Sb 3+ Perovskite scintillator screens, such as (PPN)2SbCl5

Q.He, C.Zhou, L.Xu, S.Lee, X.Lin, J.Neu, M.Worku, M.Chaaban, B.Ma, Highly Stable Organic Antimony Halide Crystals for X-ray Scintillation, ACS Materials Lett., 2020, 2, 633–638

[0004] Therefore, studying organic-inorganic hybrid perovskite glass with high transparency, good scintillation and imaging capabilities, large area coverage and controllable shape is of great significance for high-energy ray imaging. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an organic-inorganic hybrid perovskite glass for high-energy radiation imaging and a preparation method thereof, which is carried out in air without the need for inert gas protection, the product is transparent under visible light, can emit bright orange light, green light or yellow light under ultraviolet light, has a wide range of linear dose rate response, low detection limit and excellent stability.

[0006] In order to solve the above technical problems, the present invention provides an organic-inorganic hybrid perovskite glass for high-energy ray imaging and a preparation method thereof, wherein the chemical formula is A x B y C z :D m , where A is an organic group containing C, H, P, O, etc.: C 18 H 15 Cl2P、C18 H 15 Br2P、C 19 H 17 Br2P、C 19 H 18 ClOP, C 20 H 18 ClOP, C 20 H 17 ClNP, C 20 H 20 BrOP, C 21 H 22 BrP、C 21 H 22 IP, C 21 H 19 OP, C 21 H 20 BrP、C 22 H 24 BrP or C 23 H 26 BrP, B is divalent metal ion Zn 2+ , C is a halogen element Cl - or Br - , D is the doping element Mn 2+ , Sb 3+ Cu + , where x=2, y=1, z=4-9, m=0-1.

[0007] The present invention also provides a method for preparing organic-inorganic hybrid perovskite glass for high-energy ray imaging, which uses a diffusion method to synthesize crystals and a low-temperature melting method to obtain transparent glass. The method includes the following steps:

[0008] The chlorides or bromides of A, B, and D are mixed in a molar ratio of 2:1:0-1 and placed in a glass bottle containing a dichloromethane solution, and ultrasonically vibrated to fully dissolve and mix the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it is allowed to stand to obtain transparent crystals. The obtained transparent crystals are placed in a crucible and heated to a molten liquid state. The molten liquid is poured into a mold and cooled and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging.

[0009] Furthermore, the AC, BC and DC are accurately weighed, uniformly mixed according to the stoichiometric ratio, added into a glass bottle containing a dichloromethane solution, and ultrasonically vibrated for 10-20 minutes to fully dissolve and mix the raw materials.

[0010] Furthermore, after the flask containing the raw material mixture is placed in ether for dissolution, it is left to stand for 2-3 days to obtain transparent crystals.

[0011] Furthermore, the transparent crystal is added into a corundum crucible, and then the crucible is placed into a muffle furnace and heated at 140-300° C. for 0.5-1 hour.

[0012] Furthermore, the molten liquid is poured into a silicone mold at room temperature and solidified.

[0013] The organic-inorganic hybrid perovskite glass material for high-energy ray imaging provided by the present invention not only has a wide range of linear dose rate response, low detection limit and excellent stability, but also is carried out in air without the need for inert gas protection. The product is transparent under visible light and can emit bright orange, green or yellow light under ultraviolet light. Compared with traditional silicate luminescent glass (melting temperature is higher than 1300°C), the melting temperature of the present invention is 140-300°C, the equipment requirements are low, and it is easy to industrialize. Because the material of the present invention does not contain rare earth, the preparation process does not need to avoid water and oxygen, which greatly reduces the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A photograph of the orange light glass prepared in Example 1 of the present invention under visible light.

[0015] Figure 2 XRD pattern of the orange glass prepared in Example 1 of the present invention after grinding.

[0016] Figure 3 Excitation spectrum of the orange light glass prepared in Example 1 of the present invention (monitoring wavelength is 602 nm).

[0017] Figure 4 The emission spectrum of the orange light prepared in Example 1 of the present invention (excitation wavelength is 376 nm).

[0018] Figure 5 The color coordinate position of the orange light glass prepared in Example 1 of the present invention.

[0019] Figure 6 Schematic diagram of the high-energy ray imaging device of the present invention. DETAILED DESCRIPTION

[0020] The present invention is further described below in conjunction with embodiments and drawings, but the scope of protection claimed by the present invention is not limited to the scope shown in the embodiments.

[0021] Example 1

[0022] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. Ether solution was added to the glass bottle containing the mixed raw materials and the mixture was allowed to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C to solidify to obtain an organic-inorganic hybrid perovskite glass for high-energy X-ray imaging.

[0023] like Figure 1 As shown in the product photos, it exhibits excellent transmittance under natural light. The crystals and glass obtained from the product were tested using an XRD powder diffractometer (Bruker D8 Advance). Figure 2 As shown in the figure, the XRD of the product transparent crystal is consistent with the high energy ray single crystal fitting diagram, and the XRD of the product glass is an amorphous glass structure. The luminescence performance of the product is tested by fluorescence spectrometer (HORIBA Jobin Yvon Inc. Fluoromax-4), as shown in the figure. Figure 3 As shown, the excitation spectrum of the product of this embodiment has a strong broadband absorption peak in the long-wave region of 250-450nm, which can effectively absorb the light emitted by the purple LED. Figure 4 The orange light emitted is between 500 and 700 nm, and both the excitation and emission come from Sb 3+ sp transition. Figure 5 As shown, the CIE coordinates are located at (x=0.5160, y=0.4625), which is exactly in the orange light area and meets the orange light lighting requirements. Figure 6 The figure shows a schematic diagram of a high-energy ray imaging device for this product. In this system, the high-energy ray source, the imaging object, (C 20 H 17 ClNP)2ZnCl2:0.3SbCl3 glass sample and CMOS camera are arranged systematically. When high-energy rays pass through the imaging object, their energy will experience different degrees of attenuation due to the different internal structures of the object. This different attenuation allows the remaining high-energy rays to convey information about the sample. Subsequently, the residual high-energy rays stimulate 2C 20 H 17 The ClNP-(1-x)ZnCl2-xSbCl3 glass sample emits light, which is then guided to the CMOS camera by a reflector, where it is captured by a data processing system. The product appearance, XRD, fluorescence spectrum and high-energy ray imaging application schematic diagram of the following embodiments of the present invention are similar to those of this embodiment and are not described one by one.

[0024] Example 2

[0025] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.8mmol (0.1090g) ZnCl2 and 0.2mmol (0.0456g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0026] Example 3

[0027] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.6mmol (0.0818g) ZnCl2 and 0.4mmol (0.0912g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0028] Example 4

[0029] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.5mmol (0.0682g) ZnCl2 and 0.5mmol (0.1141g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0030] Example 5

[0031] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.4mmol (0.0545g) ZnCl2 and 0.6mmol (0.1369g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0032] Example 6

[0033] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.3mmol (0.0409g) ZnCl2 and 0.7mmol (0.1597g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0034] Example 7

[0035] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.2mmol (0.0273g) ZnCl2 and 0.8mmol (0.1825g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0036] Example 8

[0037] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.1mmol (0.0136g) ZnCl2 and 0.9mmol (0.2053g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0038] Example 9

[0039] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 150°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0040] Example 10

[0041] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 160°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0042] Embodiment 11

[0043] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 170°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0044] Example 12

[0045] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 180°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0046] Example 13

[0047] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 190°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0048] Embodiment 14

[0049] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 200°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0050] Embodiment 15

[0051] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 220°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0052] Example 16

[0053] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 240°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0054] Embodiment 17

[0055] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 260°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0056] Embodiment 18

[0057] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 280°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0058] Embodiment 19

[0059] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 300°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0060] Embodiment 20

[0061] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.8mmol (0.1090g) ZnCl2 and 0.2mmol (0.0456g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0062] Embodiment 21

[0063] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.6mmol (0.0818g) ZnCl2 and 0.4mmol (0.0912g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0064] Embodiment 22

[0065] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.5mmol (0.0682g) ZnCl2 and 0.5mmol (0.1141g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0066] Embodiment 23

[0067] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.4mmol (0.0545g) ZnCl2 and 0.6mmol (0.1369g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0068] Embodiment 24

[0069] 2 mmol (0.6664 g) of solid raw material C 18 H 15Cl2P, 0.3mmol (0.0409g) ZnCl2 and 0.7mmol (0.1597g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0070] Embodiment 25

[0071] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.2mmol (0.0273g) ZnCl2 and 0.8mmol (0.1825g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0072] Embodiment 26

[0073] 2 mmol (0.6664 g) of solid raw material C 18 H 15Cl2P, 0.1mmol (0.0136g) ZnCl2 and 0.9mmol (0.2053g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0074] Embodiment 27

[0075] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 150°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0076] Embodiment 28

[0077] 2 mmol (0.6664 g) of solid raw material C 18 H 15Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 160°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0078] Embodiment 29

[0079] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 170°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0080] Embodiment 30

[0081] 2 mmol (0.6664 g) of solid raw material C 18 H 15Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 180°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0082] Embodiment 31

[0083] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 190°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0084] Embodiment 32

[0085] 2 mmol (0.6664 g) of solid raw material C 18 H 15Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 200°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0086] Embodiment 33

[0087] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 220°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0088] Embodiment 34

[0089] 2 mmol (0.6664 g) of solid raw material C 18 H 15Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 240°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0090] Embodiment 35

[0091] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 260°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0092] Embodiment 36

[0093] 2 mmol (0.6664 g) of solid raw material C 18 H 15Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 280°C for 0.5 hours. The molten liquid was then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0094] Embodiment 37

[0095] 2 mmol (0.6664 g) of solid raw material C 18 H 15 Cl2P, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0684g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 300°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0096] Embodiment 38

[0097] 2 mmol (0.8442 g) of solid raw material C 18 H 15Br2P, 0.8mmol (0.1802g) ZnBr2 and 0.2mmol (0.0723g) SbBr3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0098] Embodiment 39

[0099] 2 mmol (0.8722 g) of solid raw material C 19 H 17 Br2P, 0.8mmol (0.1802g) ZnBr2 and 0.2mmol (0.0723g) SbBr3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0100] Embodiment 40

[0101] 2 mmol (0.6574 g) of solid raw material C 19 H 18ClOP, 0.8mmol (0.1090g) ZnCl2 and 0.2mmol (0.0456g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0102] Embodiment 41

[0103] 2 mmol (0.6815 g) of solid raw material C 20 H 18 ClOP, 0.8mmol (0.1090g) ZnCl2 and 0.2mmol (0.0456g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0104] Embodiment 42

[0105] 2 mmol (0.7755 g) of solid raw material C 20 H 20BrOP, 0.8mmol (0.1802g) ZnBr2 and 0.2mmol (0.0723g) SbBr3 are accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation is used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it is left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals are placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid is then poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0106] Embodiment 43

[0107] 2 mmol (0.7705 g) of solid raw material C 21 H 22 BrP, 0.8mmol (0.1802g) ZnBr2 and 0.2mmol (0.0723g) SbBr3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0108] Embodiment 44

[0109] 2 mmol (0.7366 g) of solid raw material C 21 H 19OP, 0.8mmol (0.1090g) ZnCl2 and 0.2mmol (0.0456g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0110] Embodiment 45

[0111] 2 mmol (0.7625 g) of solid raw material C 21 H 20 BrP, 0.8mmol (0.1802g) ZnBr2 and 0.2mmol (0.0723g) SbBr3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0112] Embodiment 46

[0113] 2 mmol (0.7986 g) of solid raw material C 22 H 24BrP, 0.8mmol (0.1090g) ZnCl2 and 0.2mmol (0.0456g) SbCl3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0114] Embodiment 47

[0115] 2 mmol (0.8266 g) of solid raw material C 23 H 26 BrP, 0.8mmol (0.1802g) ZnBr2 and 0.2mmol (0.0723g) SbBr3 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is orange and transparent under natural light and emits bright orange light under ultraviolet light. The appearance, XRD pattern, fluorescence spectrum and high-energy ray imaging application schematic diagram of the orange light glass are basically similar to those of Example 1.

[0116] Embodiment 48

[0117] 2 mmol (0.6755 g) of solid raw material C 20 H 17ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0377g) MnCl2 were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is green and transparent under natural light and emits bright green light under ultraviolet light. The appearance, XRD pattern, and high-energy ray imaging application schematic diagram of the green light glass are basically similar to those of Example 1.

[0118] Embodiment 49

[0119] 2 mmol (0.6755 g) of solid raw material C 20 H 17 ClNP, 0.7mmol (0.0954g) ZnCl2 and 0.3mmol (0.0297g) CuCl were accurately weighed and added to a glass bottle containing a dichloromethane solution. Ultrasonic oscillation was used for 20 minutes to fully dissolve the raw materials. After adding ether solution to the glass bottle containing the mixed raw materials, it was left to stand for 3 days to obtain transparent crystals. The obtained transparent crystals were placed in a crucible and heated to a molten liquid state at 140°C for 0.5 hours. The molten liquid was poured into a silica gel mold at 25°C and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging. The product is yellow and transparent under natural light and emits bright yellow light under ultraviolet light. The appearance, XRD pattern and high-energy ray imaging application schematic diagram of the yellow light glass are basically similar to those of Example 1.

[0120] The present invention is an organic-inorganic hybrid perovskite glass for high-energy ray imaging and a preparation method thereof. The product not only has a wide range of linear dose rate response, a low detection limit and excellent stability, but also is carried out in air without the need for inert gas protection. The product is transparent under visible light and can emit bright orange, green or yellow light under ultraviolet light. Compared with traditional silicate luminescent glass (melting temperature is higher than 1300°C), the melting temperature of the present invention is 140-300°C, the equipment requirements are low, and it is easy to industrialize. Because the material of the present invention does not contain rare earths, the preparation process does not need to avoid water and oxygen, which greatly reduces the production cost.

[0121] The above embodiments describe the implementation methods of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. An organic-inorganic hybrid perovskite glass for high-energy ray imaging, characterized in that The chemical formula is A x B y C z :D m The product has a wide range of linear dose rate response, low detection limit and excellent stability in high-energy radiation applications, making it an ideal choice for high-energy radiation imaging.

2. The organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claim 1, characterized in that A is an organic group C 18 H 15 Cl2P、C 18 H 15 Br2P、C 19 H 17 Br2P、C 19 H 18 ClOP, C 20 H 18 ClOP, C 20 H 17 ClNP, C 20 H 20 BrOP, C 21 H 22 BrP、C 21 H 22 IP, C 21 H 19 OP, C 21 H 20 BrP、C 22 H 24 BrP or C 23 H 26 One or more of BrP.

3. The organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claim 1, characterized in that B is metal ion Zn 2+ .

4. The organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claim 1, characterized in that C is a halogen element Cl - or Br - , D is the doping element Mn 2+ , Sb 3+ Cu + .

5. The organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claim 1, characterized in that: Wherein x=2, y=1, z=4-9, m=0-1.

6. A method for preparing an organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claims 1-5, characterized in that: Crystals are synthesized by diffusion method, and transparent glass is obtained by low-temperature melting method. Specifically, the chlorides or bromides of A, B, and D are accurately weighed and mixed, placed in a glass bottle containing a dichloromethane solution, and ultrasonic oscillation is used. After adding ether solution to the glass bottle containing the mixed raw materials and letting it stand, transparent crystals are obtained, and the obtained transparent crystals are placed in a crucible and melted into a liquid state. The molten liquid is poured into a mold and cooled and solidified to obtain an organic-inorganic hybrid perovskite glass for high-energy ray imaging.

7. A method for preparing an organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claims 1-5, characterized in that: The ratio of chloride or bromide of A, B and D is 2:1:0-1.

8. A method for preparing an organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claims 1-5, characterized in that: Place the chloride or bromide mixture of A, B and D into a glass bottle containing dichloromethane solution and ultrasonically vibrate for 10-20 minutes to fully dissolve and mix the raw materials.

9. A method for preparing an organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claims 1-5, characterized in that: The open glass bottle was placed in an ether solution and allowed to stand for 2-3 days, during which transparent crystals were observed to slowly precipitate.

10. A method for preparing an organic-inorganic hybrid perovskite glass for high-energy ray imaging according to claims 1-5, characterized in that: The transparent crystal is added into a corundum crucible, and then the crucible is placed into a muffle furnace and heated at 140-300° C. for 0.5-1 hour to melt into a liquid state. After being taken out, the crucible is poured into a silica gel mold at room temperature to cool and solidify into transparent glass.